MANAGEMENT OF READING HOUSE AS AN EFFORT TO INCREASE THE COMMUNITY’S READING INTEREST IN WEST PONTIANAK SUB-DISTRICT, PONTIANAK CITY - Mliani, Meliani E1012131062; Haryaningsih, Sri; Martinus, Martinus (FISIP Universitas Tanjungpura, 2021)
This research aimed to analyze the management of reading house as an effort to increase the community's reading interest in West Pontianak Sub-District, Pontianak City, namely in the factors of planning, organizing, directing and supervising. The method used in this research was qualitative of descriptive research. According to Terry in The Liang Gie (2000: 21), management activities or functions include: 1) Planning: it can be concluded that all efforts to achieve goals must be seen as a process. Therefore, in order for the achievement of the final goal to be guaranteed, phasing is required, both in the sense of phasing in the achievement of its parts and phasing in the sense of periodization. 2) Organizing: it can be concluded that the managers of reading house in West Pontianak Sub-District are open and friendly in establishing communication with visitors. The officers are willing to help visitors who are in need of certain books. 3) Briefing: it can be concluded that the process of procuring and filling in the workforce is actually sufficient, but the reading house needs to add staff who are library graduates. However, it is difficult to fulfill because the librarian profession is not very popular.gement, Reading House, Improvement, Reading Interest, West Pontianak Sub-District.